Implementation of Public Services in E-Government-Based Parking Management at the Palangka Raya City Transportation Department in Achieving Good Governance - Birowo, Rendy Rahmatullah; Nugroho, Ani; Heriamariaty, Heriamariaty (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2025)
In the era of digitalization, optimizing public services has become a crucial aspect of achieving good governance. One of the innovations in public service is the implementation of e-government in parking management. Palangka Raya City faces challenges in parking management, such as disorder, congestion, and potential revenue leakage. To address these issues, the Palangka Raya City Transportation Department has begun implementing an e-government-based parking system to enhance transparency, efficiency, and accountability. However, challenges remain, including infrastructure readiness, human resource skills, and public acceptance of the digital system. This study aims to evaluate the effectiveness of e-government implementation in parking management and its contribution to the quality of public services and good governance. A qualitative approach with a case study method is used in this research. Data collection techniques include interviews, field observations, and document analysis. Descriptive analysis is employed to interpret findings and provide insights into the implementation of the e-government-based parking system. The results indicate that the e-government-based parking system in Palangka Raya has improved transparency and regional revenue management. However, challenges such as inadequate infrastructure, limited digital literacy, and resistance from parking operators remain obstacles. This study recommends enhancing technological support, providing training for stakeholders, and conducting awareness campaigns to ensure the smooth adoption of the digital parking system. The results of this research contribute to the development of e-government policies in other sectors by emphasizing strengthening infrastructure, improving human resource competencies, integrating digital services, and developing evidence-based policies to improve effectiveness, transparency, and responsiveness to community needs